Numerical Investigation of Sand Particle Erosion in Long Radius Elbow for Multiphase Flow - Khan, M.R. (Springer, 2020)
Solid particle erosion is predominant in hydrocarbon production, drilling and minerals processing industries. Erosion may be cause by the impact of particles of various sizes, shapes, and hardness at different velocities and trajectories. Sand particles transported in multiphase flow pipelines poses erosion threat, which is one of the current flow assurance challenges in hydrocarbon production process. In the midst of them, pipe blockage and erosion issues emerge most important. Erosion is a material removal process which disintegrates material from the flow lines because of continuous sand particle impacts. Eroded pipelines affects operating safety as well as increasing operating cost. Hence, it is vital to comprehend parameters involvement to understand the erosion physics. Recently, computational fluid dynamics (CFD) along with different intrusive and non-intrusive techniques have been widely employed for erosion modeling and failure assessment. In this paper, we highlight the investigation directed to quantify sand particles erosion in long radius elbow configuration for multiphase flow conditions utilizing CFD by implementing empirical and semi-empirical erosion models. Â© 2020, Springer Nature Singapore Pte Ltd.